The Effect of Teacher’s Pedagogical Competence on Students’ Learning Achievement - Fatmawada S; Rani Maswati; Krismayati Krismiyati (PINISI Discretion Review, 2020)
This study aims to determine and explain the effect of teacher pedagogical competence on students achievement in the Office Management Automation Department of YAPIS Biak Vocational High School. This study uses an associative approach with descriptive statistical data analysis techniques with percentage, mean and standard deviation and statistical analysis of inference by using data normality tests, product moment correlations, and simple linear regression. The results of this study state that teacher’s pedagogical competence significantly influences the students achievement, therefore it is recommended that school personnel, especially school principals and teachers, should improve the quality of teacher pedagogical competencies, so that student achievement can be better for the achievement of educational goals at school.